Basal cell carcinoma: variation in invasion depth by subtype, sex, and anatomic site in 4,565 cases - John H. Pyne; Esther Myint; Elizabeth M. Barr; Simon P. Clark; Ruihang Hou (Mattioli1885, 2018)
Background: The depth of invasion by basal cell carcinoma (BCC) subtypes varies. Objective: To investigate BCC invasion depth variation by subtype and anatomic site. Method: A prospective consecutive case series of excised BCC from 2009 to 2014 in a single Australian clinic. Results: Descending mean depths for a total of 4,565 BCC cases by subtype were as follows: nodulocystic, 1.9 mm (n = 84, 95% CI: 1.70-2.03, P = 0.66); nodular, 1.6 mm (n = 947, 95% CI: 1.53-1.63, P < 0.0001); aggressive, 1.5 mm (n = 925, 95% CI: 1.44-1.59, P < 0.0001); superficial combined with nodular, 0.9 mm (n = 1,081, 95% CI: 0.83-0.90, P < 0.0001); and superficial, 0.3 mm (n = 1,528, 95% CI: 0.32-0.36, P < 0.0001). Deeper invasion was associated with increased chronic sunlight exposed sites. The deepest aggressive BCCs occurred on the neck with a mean depth of 1.8 mm (n = 46, 95% CI:1.47-2.21). Conclusion: We found significant differences in the depth of invasion for BCCs by sex, subtype, and anatomic site. For BCC with characteristics matching this study, overall adequate microscopic excision depths are proposed: superficial, 1.0 mm; superficial combined with nodular, 2.0 mm; nodular, 3.0 mm; and aggressive, 3.0 mm.